Selected Decisions (1st Ed). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1962)
This paper explains various selected decisions of the IMF's Executive Directors. The IMF has examined certain problems relating to the adjustment of its holdings of fluctuating currencies and to transactions and computations involving such currencies and has come to several conclusions. The IMF does not intend to apply the rules set forth in in the section II to its holdings of members' currencies having fluctuating rates when there is no practical interest for the IMF or members to do so. Whenever the IMF revalues its holdings of a fluctuating currency under paragraph 3, it will establish an account receivable or an account payable in respect of the amount of the currency payable by or to the member under Article IV, Section 8. Despite the improvement in the payments position of many members, sound gold and exchange policy of members continues to require that to the maximum extent practicable, gold should be held in official reserves rather than go into private hoards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet